Artificial and Live Actors in Luigi Pirandello’s Play Giants of the Mountain - Alexandra M. Bibikova (Studia Litterarum)
The article discusses the concept of replacing a stage actor with an automaton, a puppet, a dummy, or a bodiless substance in the last unfinished play by Luigi Pirandello, Giants of the Mountain (1931–1936). The interaction of human and non-human actors in the analyzed play illustrates the idea of the playwright about the relativity of life and art, the real and the fantastic that have no clear-cut boundaries between them. Pirandello was attracted by the contradiction between the appearance (“mask”) and the essence (“face”) of a person, as well as by the likening of people to puppets devoid of any individuality. In his last play, the playwright see dolls and materializing spirits created by the space itself and the power of poetry as the highest expression of art, and he continues the already established tradition. Among the trends that influenced Pirandello’s vision of the artificial body in the work of art are the theater of the “grotesque,” futurism, intellectual and symbolist drama, and the Sicilian tradition of the puppet theater. The paper also highlights scenic interpretations of Pirandello’s puppets in the following performances of the play Giants of the Mountain: Strehler (Milan) 1947, 1966 and 1994, Missiroli (Turin) 1979, Kamenkovich and Agureeva (Moscow) 2014, Latini (Bologna) 2018.